2018
DOI: 10.31026/j.eng.2018.12.04
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Lead-Acid Battery Plastic Lightweight Concrete

Abstract: This study investigates the possibility of using waste plastic as one of the components of expired lead-acid batteries to produce lightweight concrete. Different percentages of lead-acid battery plastic were used in the production of lightweight concrete. The replacements were (70, 80 and 100%) by volume of the fine and coarse aggregate. Results demonstrated that a reduction of approximately 23.6% to 35% in the wet density was observed when replacement of 70% to 100% of the natural aggregate by lead-acid batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Moreover, experimental findings obtained from some scholars demonstrated that concrete might be engaged in multiple practical construction settings thanks to the addition of waste plastic and amended thermal insulation [82][83][84][85][86][87][88].…”
Section: Overview Of Concrete's Thermal Properties Considering the En...mentioning
confidence: 99%
“…Moreover, experimental findings obtained from some scholars demonstrated that concrete might be engaged in multiple practical construction settings thanks to the addition of waste plastic and amended thermal insulation [82][83][84][85][86][87][88].…”
Section: Overview Of Concrete's Thermal Properties Considering the En...mentioning
confidence: 99%